Project on Human Development in Chicago Neighborhoods (PHDCN): Employment and Income Interview, Wave 1, 1994-1995 - Earls, Felton J. ([Verlag nicht ermittelbar], 2005)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. The Employment and Income Interview was an atypical measure in that its primary concern was not to evaluate the developmental circumstances but rather to assess the economic circumstances surrounding the subjects. The Employment and Income Interview was administered to the subjects' primary caregivers for Cohorts 0, 3, 6, 9, 12, and 15 and to the subjects themselves for Cohort 18. The Employment and Income Interview was developed specifically for the PHDCN Longitudinal Cohort Study with the intent of combining the employment and income data obtained with educational status data to create socioeconomic stratifications for the respondents. The Employment and Income Interview sought to obtain data describing the respondent's current or most recent employment and that of his or her partner. The Employment and Income Interview also sought information regarding primary income and additional sources of income as well total working hours, proximity to work, and means of transportation to work for both the respondent and his or her partner.